PEMBERDAYAAN PETANI MELALUI INOVASI PRODUK OLAHAN JAMBU KRISTAL DAN DIGITAL MARKETING DESA PATUKGAWEMULYO KEBUMEN - Astuti, Dwi Puji; Wahyuningsih, Wahyuningsih; Jaenudin , Ahmad (Jurnal Abdi Insani, 2025)
The agricultural sector in Kebumen Regency contributes significantly to the regional economy, particularly through crystal guava commodities. Patukgawemulyo Village, Mirit Subdistrict, is recognized as a production center of crystal guava with high yields; however, the selling price of fresh fruit tends to be low and unstable. This condition is further exacerbated by farmers’ limited ability in product diversification, marketing strategies, and business management, resulting in suboptimal economic potential. This community service program aimed to enhance the capacity of farmer groups in production, marketing, and agribusiness management based on crystal guava commodities. A participatory approach was applied, actively involving 30 members of the Margo Mulyo Farmer Group through planning, implementation, and follow-up stages. The training focused on two main aspects: product innovation and marketing strategies. Participants were trained to produce various value-added crystal guava-based products. In addition, marketing training covered branding, labeling, packaging design, and the use of digital media to expand market reach. The results indicated an improvement in participants’ technical skills in guava processing, successful product diversification that extended fruit shelf life, and enhanced understanding of digital marketing strategies. The partners also developed a product identity through basic labeling and initiated online marketing. Thus, this program contributes to strengthening the independence of farmer groups and supporting the development of creative economy based on local potential. Continuous mentoring is recommended to ensure product innovation sustainability and strengthen digital marketing efforts.